In quest of the historical Adam: a Biblical and scientific exploration - Craig, William Lane (William B. Eerdmans Publishing Company, 2021)
Intro -- Title Page -- Copyright -- Dedication -- Contents -- List of Figures -- Preface -- List of Abbreviations -- Part 1: The Importance of the Historical Adam -- 1. What Is at Stake -- Part 2: Biblical Data concerning the Historical Adam -- 2. The Nature of Myth -- 3. Are the Primaeval Narratives of Genesis 1-11 Myth? (Part 1) -- 4. Are the Primaeval Narratives of Genesis 1-11 Myth? (Part 2) -- 5. Is Genesis 1-11 Mytho-History? -- 6. Are Myths Believed to Be True? -- 7. Adam in the New Testament -- Part 3: Scientific Evidence and the Historical Adam -- 8. Scientific and Philosophical Preliminaries -- 9. The Evidence of Palaeoneurology -- 10. The Evidence of Archaeology (Part 1) -- 11. The Evidence of Archaeology (Part 2) -- 12. Locating the Historical Adam -- Part 4: Reflections on the Historical Adam -- 13. Putting It All Together -- Bibliography.